Acute Appendicitis Complicated by Pylephlebitis: A Case Report - Ricardo Castro; Teresa Fernandes; Maria I. Oliveira; Miguel Castro (Case Reports in Radiology)
Pylephlebitis is defined as septic thrombophlebitis of the portal vein. It is a rare but serious complication of an intraabdominal infection, more commonly diverticulitis and appendicitis. It has an unspecific clinical presentation and the diagnosis is difficult. The authors report a case of a 21-year-old man with acute appendicitis complicated by pylephlebitis. The diagnosis was made with contrast enhanced CT.